The Land Use and Land Cover Classification on the Urban Area - Mahdi, Alaa S. (Iraqi Journal of Science, 2022)
The Land Use/ Land Cover (LULC) is an essential application in many remotely sensed projects and problems. Land use is simply man-made objects such as urban, road complex targets, etc., while land covers are defined as any target and phenomenon that appear neutral. The LULC study is essential for all current and future engineering projects, as it shows the nature of the land's components, which is evident in studying and modernizing residential areas. One of the essential operations for studying LULC is the heterogeneity detection and classification calculations of satellite images and topographic maps. A part of the Baghdad, Iraq region was selected for the Landsat satellite group at different periods to detect variance and make classifications for extracting and calculating ​​the changes. Many digital techniques were used to extract the results, such as; digital change detection and two classification methods. The study showed a significant decrease in the vegetation cover areas after 2015 and the expansion of buildings and unincorporated slums due to the housing crisis. The digital methods and results were evaluated using the ENVI (Environment for Visualizing Images) ver. 4.5 and written subroutines in visual basic 6.0.